Post-stroke cognitive impairment and fatigue in patients with white matter hyperintensities. A prospective cohort study - Joakim Ölmestig; Viktor Frederik Idin Sørensen; Ingrid Grimsgaard; Birgitte Fagerlund; Christina Kruuse (Cerebral Circulation - Cognition and Behavior)
Background: Cognitive impairment, depression, and fatigue are often neglected symptoms post-stroke. This study aimed to identify how white matter hyperintensity (WMH), a marker for cerebral small vessel disease (CSVD), is associated with post-stroke cognitive impairment, fatigue, and depression. Methods: This prospective cohort study included participants admitted with stroke or transient ischemic attack. Participants were classified into two groups based on WMH on magnetic resonance imaging (MRI) using the Fazekas scale (0–1: no CSVD, 2–3: CSVD). Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA), Symbol Digit Modalities Test (SDMT), and Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) in the acute stroke phase (≤14 days) and three months post-stroke. Fatigue and depression were evaluated with the Fatigue Severity Scale (FSS) and the Beck Depression Inventory-II (BDI-II). Results: Two hundred and fifty-six participants were included with MRI. A high Fazekas score was associated with lower baseline SDMT (-4.17 ± 1.48, p = 0.005, padj = 0.019), three-months SDMT (-3.56 ± 1.66, p = 0.034, padj = 0.103), and higher baseline FSS (0.78 ± 0.26, p = 0.003, padj = 0.011) independently of age. There was no association between the Fazekas score and MoCA or BDI-II. Conclusion: These findings highlight the association between WMH, lower processing speed on the SDMT test in the acute stroke phase, and higher fatigue post-stroke. We propose that the WMH burden should be considered in all patients admitted with stroke or transient ischemic attack to identify those at increased risk of post-stroke cognitive impairment and fatigue.